Analisis Hukum Pengawasan Pelaksanaan Tender Proyek Pemerintah Daerah Dengan Pihak Swasta Dalam Perspektif Hukum Persaingan Usaha Di Kota Palembang - Zainal Abidin; Supardiansah; Syamsuddin; Marsudi Utoyo (Lex Stricta : Jurnal Ilmu Hukum, 2024)
This study examines how supervision is carried out on local government project tenders involving private parties in Palembang City, from the perspective of business competition law. The study focuses on the role of the Regional Representative Council (DPRD) and related agencies in ensuring that the tender process is transparent, fair, and free from monopolistic practices and collusion. The study uses a normative juridical approach combined with case studies. The results indicate that although the oversight mechanisms have followed applicable regulations, there is still potential for unhealthy competition, particularly due to weak oversight during the administrative and bid evaluation stages. Therefore, it is necessary to strengthen technical regulations, enhance the competence of oversight personnel, and foster closer inter-agency collaboration to promote healthy competition and support optimal regional development.